The Essence Of School Culture In Improving Teacher Performance In Smp Negeri 1 Kalirejo, Lampung Central Regency - Rusmiyati; Siti Patimah; Koderi; Wan Jamaludin; Muhammad Akmansyah; Eti Hadiati (CV. Inara, 2021)
The purpose of this study was to determine the essence of school culture in improving teacher performance at SMP Negeri 1 Kalirejo, Central Lampung Regency. Data was collected by observation, interviews, and documentation.The subjects of this study were principals, vice principals, teachers, administrative staff, assistants, and security staff. The results showed that school culture, namely the regularity of behavior, adopted norms, dominant values, philosophy, rules and school climate, had an effect on improving teacher performance.